(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
During the first year of the new Peronist government of President Alberto Fernández, Argentina had to face social and economic emergencies that worsened following the explosion of the infection from Covid-19. The executive has tried to maintain social cohesion, reaffirmed the role of the State in the economic field and conducted a fundamental negotiation for the restructuring of its foreign debt. However, the political agenda has suffered an important slowdown and the prolonged quarantine has brought back tensions that have never entirely abated. But the pandemic crisis could also have been an opportunity to start rethinking leadership and priorities within the two current political fields